The Pre-kautilyan Period: a sustainable model through ancient economic ideas and practices - Satish Deodhar; Sriram Balasubramanian (European Historical Economics Society (EHES), 2020)
A number of studies have been conducted in the recent past throwing light on Kautilya's contribution to economic policy much earlier than contributions from western scholars. In his treatise Arthashastra, Kautilya informs that his contribution was based on received knowledge and gives credit to his predecessors whose specialized works have been lost with the passage of time. Fortunately, however, this knowledge is interspersed in ancient Vedic and Puranic treatises. In this paper, we conceptualize a 5-pillar sustainable economic model through the lens of the ideas emanating in these ancient treatises. These include individual economic and social well-being through Dharma; collective strength through governance mechanisms; wealth creation through Artha; sustaining wealth through market facilitation, labor and private sector participation; and building institutional capacity through coinage, money creation and public finance. Cumulatively, the 5-pillar model resonates very well with some of the Kautilyan concepts as well as modern economic policy trends.
Keywords: B11; B15; 330; Ancient Indian Texts; Arthashastra; Ramayana; Mahabharata; Economic History; History of Economic Thought; India; Kautilya; Political Economy; Sanskrit; Vedas